In-situ monitoring of early hydration of clinker and Portland cement with optical fiber excitation Raman spectroscopy. (September 2020) - Yue, Yanfei; Wang, Jing Jing; Basheer, P.A. Muhammed; Bai, Yun
Abstract: This paper explores the potential of using optical fiber Raman spectroscopy for continuously monitoring the early hydration of cement thanks to its superb capacities for characterizing wet samples and poorly-structured calcium-silicate-hydrate (C-S-H) as well as its excellent remote sensing competence. A bespoke optical fiber excitation Raman spectrometer with a 632.8 nm laser wavelength under an "optical fiber excitation + spectrometer objective collection" configuration was established and applied. The ongoing hydration of a clinker and a Portland cement (PC) was then monitored during their first 8 h of hydration. The main hydration products, in particular, C-S-H and ettringite & monosulfate (AFt & AFm), have been successfully identified and continuously monitored in situ . The findings from the optical fiber Raman were well supported by bench-mounted Raman, X-ray Diffraction (XRD) and Isothermal Conduction Calorimetry (ICC) tests. The results presented in this paper show a great potential of optical fiber Raman spectroscopy for future civil engineering applications. Highlights: Optical fiber Raman spectroscopy is a promising technique for in situ monitoring early hydration of clinker and Portland cement (PC) due to its superb capacities for characterizing wet samples and poorly-structured calcium-silicate-hydrates (C-S-H). The evolution of C-S-H in the hydration of clinker and AFt/AFm in the hydration of Portland cement has been successfully traced respectively, by optical fiber excitation Raman spectroscopy. Optical fiber Raman spectroscopy demonstrated huge potential for monitoring the servicing condition of concrete structures on site .